2020
DOI: 10.1186/s41182-020-0193-2
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica and amoebic liver abscess in northern Sri Lanka: a public health problem

Abstract: Entamoeba histolytica (E. histolytica) is a facultative protozoan parasite implicated in amoebic liver abscesses (ALA), the most common extraintestinal manifestation of this infection. E. histolytica is endemic to subtropical and tropical countries and has been a major public health concern in northern Sri Lanka (SLK) for the last three decades. This has been attributed to a multitude of factors such as poor sanitation, hygiene, male sex, middle age, overcrowding, unsanitary practices in the production of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 106 publications
0
36
0
Order By: Relevance
“…Twenty-six studies reported on the mitigating role of religion during the early stage of COVID-19 (Ahmed & Memish, 2020 ; Al-Rousan & Al-Najjar, 2020 ; Ali & Alharbi, 2020 ; Atique & Itumalla, 2020 ; Crubézy & Telmon, 2020 ; Ebrahim & Memish, 2020a , 2020b ; Escher, 2020 ; Frei-Landau, 2020 ; Gautret et al, 2020 ; Ha, 2020 ; Hong & Handal, 2020 ; Iqbal et al, 2020 ; Kim et al, 2020 ; McCloskey, et al, 2020a , 2020b ; Memish et al, 2020 ; Muurlink & Taylor-Robinson, 2020 ; Quadri, 2020 ; Tarimo & Wu, 2020 ; Waitzberg et al, 2020 ; Weinberger-Litman et al, 2020 ; Wildman et al, 2020 ; Wong et al, 2020 ; Yezli & Khan, 2020a , 2020b ) (Appendix 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-six studies reported on the mitigating role of religion during the early stage of COVID-19 (Ahmed & Memish, 2020 ; Al-Rousan & Al-Najjar, 2020 ; Ali & Alharbi, 2020 ; Atique & Itumalla, 2020 ; Crubézy & Telmon, 2020 ; Ebrahim & Memish, 2020a , 2020b ; Escher, 2020 ; Frei-Landau, 2020 ; Gautret et al, 2020 ; Ha, 2020 ; Hong & Handal, 2020 ; Iqbal et al, 2020 ; Kim et al, 2020 ; McCloskey, et al, 2020a , 2020b ; Memish et al, 2020 ; Muurlink & Taylor-Robinson, 2020 ; Quadri, 2020 ; Tarimo & Wu, 2020 ; Waitzberg et al, 2020 ; Weinberger-Litman et al, 2020 ; Wildman et al, 2020 ; Wong et al, 2020 ; Yezli & Khan, 2020a , 2020b ) (Appendix 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Findings on policy recommendations for religious groups to combat COVID-19 are summarized in Table 1 . A total of 26 articles provided recommendations on controlling and managing COVID-19 (Ahmed & Memish, 2020 ; Al-Rousan & Al-Najjar, 2020 ; Atique & Itumalla, 2020 ; Chirico & Nucera, 2020 ; Crubézy & Telmon, 2020 ; Ebrahim & Memish, 2020a , 2020b ; Escher, 2020 ; Gautret et al, 2020 ; Greene et al, 2020 ; Ha, 2020 ; Hashmi et al, 2020 ; Hong & Handal, 2020 ; Iqbal et al, 2020 ; Jaja et al, 2020 ; Kang, 2020 ; Koenig, 2020b ; Mat et al, 2020 ; McCloskey, et al, 2020b ; Memish et al, 2020 ; Quadri, 2020 ; Tarimo & Wu, 2020 ; Thompkins et al, 2020 ; Wong et al, 2020 ; Yezli & Khan, 2020a , 2020b ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings were also noted by Tharmaratnam et al and Kantor et al in their study. 4,11 From the very old days, the laboratory diagnosis of E. histolytica has always been based on direct microscopic examination of stool samples showing distinct protozoan morphology. 12 Currently, however, usage of the direct microscopy-based identification techniques to differentiate among protozoa with similar morphological features like E. coli, E. moshkovskii, E. dispar, and E. hartmanni is seemingly unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…Another study identified 346 molecular and immunologically confirmed patients with amebic liver abscess, all seen at the Teaching Hospital, Jaffna, within 3 years [ 14 ]. A more recent study identified E. histolytica as a public health problem in northern Sri Lanka, owing to poor sanitation and poor hygienic practices [ 15 ].…”
Section: Discussionmentioning
confidence: 99%